2003
DOI: 10.1021/ja036000r
|View full text |Cite
|
Sign up to set email alerts
|

Homolytic vs Heterolytic Paths in the Photochemistry of Haloanilines

Abstract: The photochemistry of 4-haloanilines and 4-halo-N,N-dimethylanilines has been studied in apolar, polar aprotic, and protic solvents. Photophysical and flash photolysis experiments show that the reaction proceeds in any case from the triplet state. It is rather unreactive in apolar media, the highest value being Phi = 0.05 for the iodoanilines in cyclohexane. Changing the solvent has little effect for iodoanilines and for the poorly reacting bromo analogue, while it leads to a variation of over 2 orders of magn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
75
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(79 citation statements)
references
References 72 publications
4
75
0
Order By: Relevance
“…The photoreactivity of 4-chloro-N,N-dimethylaniline (1), previously studied in organic solvents of different polarity, [10] was thus explored in some ILs. Specifically, we chose five methylalkylimidazolium salts (2 a-e) as a homogeneous series with similar polarity, polarizability, and hydrogenbond basicity and acidity by varying only the length of the alkyl chain (butyl or hexyl) and the counterion (at any rate, a non-nucleophilic anion, namely…”
Section: Introductionmentioning
confidence: 99%
“…The photoreactivity of 4-chloro-N,N-dimethylaniline (1), previously studied in organic solvents of different polarity, [10] was thus explored in some ILs. Specifically, we chose five methylalkylimidazolium salts (2 a-e) as a homogeneous series with similar polarity, polarizability, and hydrogenbond basicity and acidity by varying only the length of the alkyl chain (butyl or hexyl) and the counterion (at any rate, a non-nucleophilic anion, namely…”
Section: Introductionmentioning
confidence: 99%
“…[34] Such reactions would explain the oxygenindependent phototoxicity of this drug [Equation (2)]. Investigations aimed to document intermolecular reaction paths are ongoing.…”
Section: Resultsmentioning
confidence: 99%
“…Insertion into the CϪH bond would lead to a highly strained compound in this case, and thus hydrogen transfer takes place instead. Indeed, in the case of the 4-aminophenyl cation it has been demonstrated that alcohols and amines act as H donors, giving a radical cation that is then reduced to the final compound [34,40,47] (Scheme 7). In this case the second step would occur intramolecularly (overall a formal hydride transfer) to give cation 11.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations